Discovery of Ancient Canoes on the Clyde (Proceedings of the Society of Antiquaries of Scotland, 1852)
John Buchanan wrote in to communicate the discovery of two canoes in the vicinity of Glasgow and the River Clyde. These two canoes accreted yet more evidence of the earliest rivercraft on the Clyde, fifteen such boats having been found in the 70 years preceding the publication of this article.